Alfred Binet : de la suggestion à la cognition, 1857-1911 - Andrieu, Bernard (1959-....); Avanzini, Guy; Clozza, Cristina; Klein, Alexandre (1984-....)
ill., couv. ill. Bibliogr. complète des oeuvres de et sur Alfred Binet p. 145-224